Astrophysical uncertainties on the local dark matter distribution and direct detection experiments - Green, Anne M. (IOP Publishing, 2017)
The differential event rate in weakly interacting massive particle (WIMP) direct detection experiments depends on the local dark matter density and velocity distribution. Accurate modelling of the local dark matter distribution is therefore required to obtain reliable constraints on the WIMP particle physics properties. Data analyses typically use a simple standard halo model which might not be a good approximation to the real Milky Way (MW) halo. We review observational determinations of the local dark matter density, circular speed and escape speed and also studies of the local dark matter distribution in simulated MW-like galaxies. We discuss the effects of the uncertainties in these quantities on the energy spectrum and its time and direction dependence. Finally, we conclude with an overview of various methods for handling these astrophysical uncertainties.